1978
DOI: 10.1016/0304-3959(78)90016-7
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of patient semantic pain descriptions to physician diagnostic judgements, activity level measures and NMPI

Abstract: A consecutive sample of chronic pain patients presenting themselves for evaluation was studied. A set of 25 bi-polar adjectives was developed from medical records of previous pain patients' descriptions of their pain. Using the Semantic Differential (S-D) method, each patient rated the extent to which his/her pain was best described by either of the adjective pairs. The S-D findings were then compared with three other data sets and those data sets were compared with each other. First, six physicians classified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
2

Year Published

1982
1982
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(17 citation statements)
references
References 7 publications
0
15
2
Order By: Relevance
“…In contrast to the above findings, Fordyce et al (1978) found only weak correspondence between patients' semantic descriptions of pain and medical diagnostic labels. They stated that it appears unlikely that choices of words by which pain is described will hold up as reliable discriminators among subgroups across a spectrum of patients, cultures, and patient selection factors.…”
contrasting
confidence: 83%
See 1 more Smart Citation
“…In contrast to the above findings, Fordyce et al (1978) found only weak correspondence between patients' semantic descriptions of pain and medical diagnostic labels. They stated that it appears unlikely that choices of words by which pain is described will hold up as reliable discriminators among subgroups across a spectrum of patients, cultures, and patient selection factors.…”
contrasting
confidence: 83%
“…If it is the case that pain and ache can be correlated with neurophysiological and anatomical structures, then in contrast to the suggestion by Fordyce (1978) it seems likely that there is a universal basis for the different distinctions employed in the pain vocabularies of different languages.…”
Section: The Main Components Of the Modelcontrasting
confidence: 49%
“…Both psychological and psychosocial interventions in addition to conventional exercise therapy may have a more positive effect on treatment outcome [80][81][82][83][84][85][86][87][88][89][90]. The targeted effect of such an approach would be the development of a sense of control over pain and the elimination of pain-avoidance mechanisms, whilst simultaneously improving overall physical fitness/function.…”
Section: Future Thoughtsmentioning
confidence: 99%
“…Therefore, psychological support contributes to not only the physical assistance that family or friends can offer, but also contributes to the self-worth of individuals experiencing an injury (e.g., Andrews & Brown, 1988;Elliott, Herrick, & Witty, 1992;Elliott & Shewchuk, 1995;Hwang, Chang, & Kasimis, 2000). Similar evidence is documented in the association of pain with decreased social, recreational, vocational, and domestic activities (e.g., Fordyce, Brena, Holcomb, Delateur, & Loeser, 1976: Kerns & Haythornthwaite, 1988Kerns & Jacob, 1993;Rudy et al, 1988).…”
Section: Resistance Factor -Intrapersonal Factorsmentioning
confidence: 66%